The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/nrl.0b013e3181618ada
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Hormonal Conditions in Epilepsy

Abstract: Epileptic patients will benefit from regular monitoring of ovarian and testicular functions. Early characterization of reproductive abnormalities encountered in patients with epilepsy will allow neurologists to properly choose and change antiepileptic medications. This will also improve patients' sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 165 publications
(216 reference statements)
0
5
0
Order By: Relevance
“…Contrasting to this decrease of bioavailable testosterone, levels of corticosterone are usually greater among individuals with acquired epilepsy compared to controls [17], [35], [53], [64]. Thus, in our model, high levels of corticosterone may decrease free testosterone, but increase E 2 levels in an age-dependent fashion.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Contrasting to this decrease of bioavailable testosterone, levels of corticosterone are usually greater among individuals with acquired epilepsy compared to controls [17], [35], [53], [64]. Thus, in our model, high levels of corticosterone may decrease free testosterone, but increase E 2 levels in an age-dependent fashion.…”
Section: Discussionmentioning
confidence: 67%
“…Male pups experience a surge of testosterone that occurs on days 18–19 of gestation and again during the first few hours after birth with a critical window from P0 to P2 [14], [52]. Emerging data show that testosterone and its active metabolites, estradiol and dihydrotestosterone, are important factors in both androgenization of the brain and the response to early life insults such as cerebral ischemia, trauma and seizures [53]. In general, clinical evidence and animal models indicate greater brain damage in newborn male compared to female following injury.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that GHSR inhibits Ca V 3.2 currents. In neurons, Ca V 3 channels control the shape and frequency of action potentials (Perez-Reyes, 2003;Zhang et al, 2013), and changes in channel activity due to alternative splicing (Murbartian et al, 2004;Latour et al, 2004) or nonsense mutations (Powell et al, 2009) are responsible for pathophysiological states, such as epilepsy (Hamed, 2008). Yet, the mechanisms that control Ca V 3 trafficking and surface membrane stability are largely unknown (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Animal and clinical studies have suggested that epilepsy itself may affect sperm quality, sexual function, and sex hormones [ 22 ]. The decline in sperm quality and sexual function in men with epilepsy may be related to the disruption of hypothalamic pituitary axons by cerebral epileptiform discharges, resulting in changes in sex hormone levels [ 17 ].…”
Section: Discussionmentioning
confidence: 99%